Effect of castration on carcass yield and composition of crossbred river buffaloes (Buffalypso) in the growth stage - Fundora, Orlando; Torres, Verena; Medina, J. L.; Sarduy, Luc?a; Gonz?lez, Mar?a Elena (Cuban Journal of Agricultural Science, 2013)
Twenty four crossbred river buffaloes (Buffalypso) were used from weaning with an initial average live weight of 135.5 kg and between 16 and 24 months of age. Animals were placed in grazing areas of natural pastures under two experimental treatments consisting of their sexual condition (castrated or not). An analysis of variance according to a completely randomized design and an analysis of covariance were applied in which as concomitant variables were used the initial live weight and the age in days, as well as the adjustment for the last variable in the carcass indicators resulting with higher coefficients. For identifying the most important variables in the performance of treatments and their variability, a multivariate analysis was employed. For the analysis of carcass yield and its components, data were transformed through arcsine ?%. Carcass yield (48.34 to 47.05 %) and their components, first quality (28.04 to 29.43 %) and second quality meats (29.35 to 28.84 %), bones (28.73 to 29.02 %) and fat (13.88 to 12.71 %) were not affected by castration. It is concluded that castration had no important effects on the studied indicators, although it is recommended to carry out new evaluations with animals at higher slaughter live weight. Key words: buffaloes, growth, carcass, grazing